Supersymmetry - Binétruy, P. (Oxford University Press, 2006)
This book is an introduction to the theory of supersymmetry, which is a cornerstone to understanding the physics of elementary particles beyond the so-called "Standard Model". Supersymmetry is the first introductory book on this modern and increasingly popular subject